Comunicação e cultura em filigranas: narrativas e produção de sentido sobre a Praça Roosevelt - Marcelino, Rosilene Moraes Alves (2018)
This thesis subject is the narrative and production of meaning from a fraction of the city of São Paulo: Praça Roosevelt. Located in the heart of the biggest city in Brazil - from the non-square to Praça da Consolação, until becoming the Roosevelt as we know it today - it represents a challange for those who studies this mix of cultures system (GRUZINSKI, 2001), an amalgam of complexity and heterogeneity that puts in relation, day and night, many scructures and intensities, becoming a land that Pinhiero (2015) identifies as trans-baroque. This trans-baroque conditions constitutes themselves as an unfinished delimited area, composed by marquetries of foreign repertoires and intertwining (at the same time inclusive and translucent) of the voices of culture. Facing a myriad of possibilites for approaching Roosevelt square, the narratives takes its place and stablishes itself as the apex from which the reflections are developed. This choice leads this research to a qualitative tone in which it is interesting to capture what, for the Roosevelt square, converges and which of its places are in relation to other social spheres, leading us to be membrane-researchers-interpretative-translators of ways in a social, discursive and cultural life. In that matter, the first chapter - "Roosevelt: assombro, escombro, promessa, quimera" - a documental and bibliographical research, contemplates the film narrative as its center and the documentaries "Palco Roosevelt" (2007) and "Roosevelt: uma praça além do concreto" (2008) as its corpora. The main goal is to get to know the meanings offered by the audiovisual productions about the square and its biggest renovation. For such, the works are decomposed into textual, imagery, sound and situational aspects, and situations and authors such as Pinheiro, Salles, Delgado and Sousa Santos are brought to reflection. The second chapter - "Para além da concretude, quiproquós citadinos" - intends to get in contact with the square's most recent history, electing two audiovisual narratives conceived after its main reform, completed in 2012: "Praça Roosevelt" (2016 documentary) and "O estilo de vida no centro" (a webseries episode produced in 2018). The topic, based on a methodological strategy composed by documental and bibliographic research, articulates considerations from authors such as Certeau, Ferrara, Laplatine, Lotman and Martín-Barbero, Morin, Pinheiro and Salles. The third chapter - "Alegria, alegria: a mosca na sopa" - confirms the effort in search of discursive threads about Praça Roosevelt, having its specific aim of sharing - in both descriptive and interpretative ways - the impressions of the field, paying attention to institutionalized speeches and reports from the residents of the square. For this step, among the authors, we have Brockmeir, Harré, Certeau, Delgado e Elias. At the fourth chapter - “Andar com fé eu vou, que a fé não costuma faiá” - we are dedicating our attention to reflect about the production of meaning emanating from certain constuitive spheres of Praça Roosevelt. Here, we look specifically to the Nossa Senhora da Consolação church, based on fieldwork carried out during the first half of 2018. In this ethnographic inspiration, there was the opportunity, for example, to approach stories of the homeless a floating population, constitutive and constituent of Praça Roosevelt. In methodological terms, this step finds anchoring in the grounded theory and bibliographical and documentary research that the contact with the field provokes. Sousa Santos (2008) and Lotman (1996) are the bases tor detailing the reality, given their perspectives about inequality, exclusion and semiotic disarmament. Finally, the fifth chapter - "'Sãopauleando': prosa, verso, música e zine" - seeks to present the lessons learned with the young people that go to Praça Roosevelt from the perspective of their life stories. This topic shares conversations in the order people were known, no scripts were involved. It is about the narrative of those who, as the floating population of Roosevelt, put into circulation narratives about the square. In each person, a different world. In each one, a lot of Roosevelts. The qualitative perspective is transversal and the authors used here are García Canclini, Morin and Santos